Ceftriaxone versus povidone iodine in preventing wound infections following biliary surgery. - Kiff, R. S. (Royal College of Surgeons of England, 1988)
The effect of either prophylactic antibiotic or wound antiseptic on bile bacteriology, wound and other postoperative sepsis has been studied in a controlled prospective randomised trial of 243 patients undergoing biliary surgery at a district general hospital. Wound infection rates were significantly less in patients given intravenous ceftriaxone (1%) at induction of anaesthesia when compared to povidone iodine sprayed into the wound at the completion of surgery (9%) (P = 0.02). In all but one patient infected wounds grew organisms identical to those cultured from the bile. There were also fewer chest and urinary infections in the ceftriaxone group but this was not statistically significant.